Selective nonlinear response preparation using femtosecond spectrally resolved four-wave-mixing - Kraack, Jan Philip; Motzkus, Marcus; Buckup, Tiago (The journal of chemical physics, 2011)
A novel method is presented to assist the assignment of vibrational coherence in the homodyne degenerate four-wave-mixing technique. The dependence of vibrational coherence dynamics on the interaction sequence of chirped pump and Stokes excitation pulses is exploited to distinguish quantum beating from polarization interference. Moreover, by combining chirped excitation and variable delays between pump and Stokes pulses, it is possible to achieve a controlled excitation of response pathways from a single electronic state and separation of population dynamics and vibrational coherence dynamics within a single response pathway. Numerical simulations are performed in the response function framework, which clearly show that such an approach applies for oscillatory contributions originated in the electronically excited state as well as in the ground state. The approach is experimentally demonstrated in three different polyatomic molecules in solution.
Gesehen am 08.07.2022